2011
DOI: 10.4067/s0716-078x2011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Conservation biology in Chile: Are we fulfilling our social contract?

Abstract: Biodiversity conservation needs to be informed by science. On this regard, scientific efforts ought to be allocated to tackle research priorities; offer sound and explicit advice, and results ought to be translated into conservation plans and programs. If such conditions are met, scientists would be fulfilling their social contract, sensu Lubchenco. In this brief essay I analyze the fulfillment of such a contract in Chile. In general, the scarce priorities set for addressing conservation issues are not conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…This suggests that the concerns that publications are targeted at academics rather than managers [9,27] may be universal to managers regardless of whether they are in developed or developing countries. Other studies have reported that managers are concerned about interpreting research for their management context [11], preferring to discuss findings with scientists [10] or colleagues [6].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the concerns that publications are targeted at academics rather than managers [9,27] may be universal to managers regardless of whether they are in developed or developing countries. Other studies have reported that managers are concerned about interpreting research for their management context [11], preferring to discuss findings with scientists [10] or colleagues [6].…”
Section: Discussionmentioning
confidence: 99%
“…This issue is exacerbated when articles are not readily available to decision-makers through open-access or agency journal subscriptions. Moreover, primary literature is often too technical for environmental managers to interpret and does not clearly articulate how the new results could assist management decisions (Fazey et al 2005;Simonetti, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a minimum, I could have formulated clear and explicit recommendations for practitioners (Memmott et al. ; Simonetti ). So, I have no reason to blame the policy‐makers and practitioners that failed to find my study in the vast ocean of published research.…”
Section: An Example Of the Failure To Communicatementioning
confidence: 99%
“…I should have considered practitioners when publishing, but seem to have forgotten that anyone outside academia might be interested. As a minimum, I could have formulated clear and explicit recommendations for practitioners (Memmott et al 2010;Simonetti 2011). So, I have no reason to blame the policy-makers and practitioners that failed to find my study in the vast ocean of published research.…”
Section: Introductionmentioning
confidence: 99%